Enhanced electromechanical performance of Si-modified lead-free BiFeO3-BaTiO3 ceramics for high-temperature piezoelectric applications - Hussein Alrobei; Muhammad Habib; Shoaib Ali; Rizwan Ahmed Malik; Muhammad Javid Iqbal; Qamar Iqbal; Fadl A. Essa; Z.M. Omara (PLoS ONE, 2025)
Environmental pollution generated by industrial wastes are deteriorating land, water, and marine life, which raises major concerns about climate change. Since environmentally friendly piezoelectric materials can generate clean energy by applying mechanical forces, they are seen as viable agents for industrial applications. In recent research work, the Si-modified 0.70Bi1.03FeO3-0.30BaTiO3 (BF30BT) environmentally friendly piezoceramics were synthesized using a solid-state method followed by a thermal quenching process. The crystalline structure, microstructure, and electromechanical characteristics were explored as a function of Si for both dopants (BC; before calcination) and additives (AC; after calcination). The result of pure BF30BT ceramic reveals a dominant rhombohedral phase exhibiting a d33 of 251 pC/N with a higher TC of 560 °C. The Si-doping gradually transformed the predominant rhombohedral phase to the rhombohedral-tetragonal mixed phase asymmetry as a result a good balance was achieved among d33 (209 pC/N), Qm (32.6), and kp (0.32%) with a high TC (465 °C). A giant-induced electric field bipolar strain of 0.39% corresponding to a large-signal piezoelectric coefficient d33* ≈  750 pm/V was perceived in Si-doped BF30BT ceramic. The defect dipoles by acceptor doping play an essential role in the enhancement of piezoelectricity. The defect dipole aligns in the spontaneous polarization and also offers restoring force for domain switching leading to high asymmetric electrostrain. This study provides a good design benchmark for a new generation of eco-friendly large-strain actuator piezoceramics.